Legal Basis of the Police’s Activity to Ensure the Safety of Road Participants in the Chinese People’s Republic - V. I. Maiorov; O. N. Dunaeva (Сибирское юридическое обозрение, 2018)
The article provides a general description of the organizational and legal model of the functioning of the police of the People’s Republic of China to ensure the safety of road users. The purpose and structuralfunctional interrelation of a number of state bodies included in the road safety system are considered: the Department of State Security at the State Council of the People’s Republic of China, the Ministry of Public Security (MOB), the transport departments of the MOB and the Traffic Police. The analysis of the laws of the People’s Republic of China “On the People’s Police” and “On measures of road safety”. Attention is focused on the high level of training requirements for the People’s Police of China. Administrative and legal sanctions for violations of road safety rules in the PRC are investigated.